Photobiology: introduction, overview and challenges - Leister, Dario (Frontiers in Photobiology, 2023)
Photobiology is a broad field of research that studies the biological effects of light and has made huge advances in understanding fundamental questions such as how Photosynthesis works and in the area of medicine, which has a direct impact on society. Various specialties of Photobiology have been proposed, and to simplify the overview, six major fields are considered here: Photophysics and Photochemistry, Photosynthesis, Photoreception, Photomedicine, Optogenetics and Optical Bioimaging, and Ecological Photobiology. In this review, an introduction, description and examples are given for each of these major research areas. Current challenges in Photobiology include the understanding of non-visual Photoreception, complex photoreceptive mechanisms and the development of novel therapeutic strategies that may depend on the results of advanced optogenetic approaches. Furthermore, the integration of Photobiology with other fields such as materials science and engineering may lead to artificial photoreceptors and bio-inspired light harvesting and artificial Photosynthesis systems. In an era of global change, understanding the effects of artificial light on organisms and ecosystems is essential to mitigate the ecological disruptions caused by artificial lighting. This non-exhaustive selection of research directions and challenges illustrates the complexity and breadth of Photobiology research.